2011
DOI: 10.4103/0253-7176.85396
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization Study of Psychotropic Drugs in Outdoor Patients in a Teaching Hospital

Abstract: Background:Psychotropic drugs have had a remarkable impact in psychiatric practice. However, their utilization in actual clinical practice, effectiveness and safety in real life situation need continuous study.Materials and Methods:A prospective cross sectional study was carried out for 6 months. Patients of all ages and both sexes were included in the study while in-patients, referred patients and patients of epilepsy were excluded. Using World Health Organization basic drug indicators, the prescribing patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
47
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 10 publications
17
47
3
2
Order By: Relevance
“…Male subjects were slightly dominating with a proportion of 1.2:1 which was similar to previous studies. 12,14,15 In the present study most common psychiatry disorder was diagnosed as schizophrenia followed by depression and bipolar disorder which was in accordance with previous studies. 12,15 We found a significant result in schizophrenia and other comorbidities of psychiatry patients but not seen in previous study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Male subjects were slightly dominating with a proportion of 1.2:1 which was similar to previous studies. 12,14,15 In the present study most common psychiatry disorder was diagnosed as schizophrenia followed by depression and bipolar disorder which was in accordance with previous studies. 12,15 We found a significant result in schizophrenia and other comorbidities of psychiatry patients but not seen in previous study.…”
Section: Discussionsupporting
confidence: 92%
“…15 Lorazepam is the most commonly prescribed in long stay wards, typically for anxiety, aggression and agitation, while clonazepam is used in mania, anti convulsive effect in subclinical epilepsy and for anti anxiety effect. 15,16,19 Curtin suggested that lorazepam is not effective in treating the acute mania when compared to clonazepam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of psychotic disorder was significantly high in the age group of 20-60 y contributing 87.34% in which 20-40 y and 41-60 y contribute to 55.69% and 31.65% respectively. The prevalence in the 20-40years age group is also reflected in a study by Pradeep Bodke et al [6] and also in many other studies [8]. The Prevalence of schizophrenia and Mental retardation with significant impairment of behaviour is significantly high in males when compared to females in the ratio of 3:2 and 6:1 respectively, while the study says there is no difference in prevalence though the incidence seems to be higher in males [9].…”
Section: Profile Of Study Participantsmentioning
confidence: 53%
“…Without the knowledge of how the drugs are being prescribed, it is difficult to suggest the measures to improve prescribing habits. 5 Retrospective drug utilization review can be used to identify problems in prescribing patterns through the analysis and interpretation of aggregate archival data on drug prescriptions. This process has no immediate effect on patient care but can identify trends and prompt interventions.…”
Section: Introductionmentioning
confidence: 99%